Arogenate dehydratases: unique roles in light-directed development during the seed-to-seedling transition in Arabidopsis thaliana - Muhammad, DurreShahwar; Alameldin, Hussien F.; Oh, Sookyung; Montgomery, Beronda L.; Warpeha, Katherine M. (Frontiers in Plant Science, 2023)
The seed-to-seedling transition is impacted by changes in nutrient availability and light profiles, but is still poorly understood. Phenylalanine affects early seedling development, thus, the role(s) of arogenate dehydratases (ADT), which catalyze phenylalanine formation, were studied in germination, and during the seed-to-seedling transition by exploring the impact of light conditions and specific hormone responses in adt mutants of Arabidopsis thaliana. ADT gene expression was assessed in distinct tissues and for light-quality dependence in seedlings for each of the six-member ADT gene family. Mutant adt seedlings were evaluated relative to wild type for germination, photomorphogenesis (blue, red, far red, white light and dark conditions), anthocyanin accumulation, and plastid development-related phenotypes. ADT proteins are expressed in a light and tissue-specific manner in transgenic seedlings. Among the analyzed adt mutants, adt3, adt5, and adt6 exhibit significant defects in germination, hypocotyl elongation, and root development responses during the seed-to-seedling transition. Interestingly, adt5 exhibits a light-dependent disruption in plastid development, similar to a phyA mutant. These data indicate interactions between photoreceptors, hormones, and regulation of phenylalanine pools in the process of seedling establishment. ADT5 and ADT6 may play important roles in coordinating hormone and light signals for normal early seedling development.